1999
DOI: 10.1038/sj.jea.7500035
|View full text |Cite
|
Sign up to set email alerts
|

High lead exposures resulting from pottery production in a village in Michoacán State, Mexico

Abstract: This paper reports findings from a screening study conducted to examine potential lead (Pb) exposures in residents of a Mexican village where Pb oxide continues to be used in ceramic pottery production. Extremely high Pb concentrations were measured in personal and indoor air samples, household surface dust samples, and household soil samples. Personal air Pb concentrations for workers performing pottery firing and glazing were up to 454 g/m 3 . Results from indoor air samples indicate that airborne Pb concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Such important discharges are also coincident with the establishment of a ceramics factory close to the Oitavén-Verdugo River mouth, which occurred around 1970. Pb is utilized in the ceramics industry for glazing (Hibbert et al, 1999;Larsson et al, 1999). The high lead concentrations detected support the conclusion that the main Pb input to the Ría de Vigo from 1970 is constituted of discharges from this ceramics factory (a point-source).…”
Section: Chronology Of Trace Metal Inputssupporting
confidence: 63%
“…Such important discharges are also coincident with the establishment of a ceramics factory close to the Oitavén-Verdugo River mouth, which occurred around 1970. Pb is utilized in the ceramics industry for glazing (Hibbert et al, 1999;Larsson et al, 1999). The high lead concentrations detected support the conclusion that the main Pb input to the Ría de Vigo from 1970 is constituted of discharges from this ceramics factory (a point-source).…”
Section: Chronology Of Trace Metal Inputssupporting
confidence: 63%
“…Guidelines for reassessing blood lead and reducing preventable exposures generally follow current American Academy of Pediatrics guidelines [54]. It is worthy to note that the guidelines for management of lead poisoning mention specifically glazed pottery and other sources which are uniquely associated with neurotoxic exposure in this population [55,56]. …”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Hirtle et al (1998) 29 have reported that signicant amounts of metals are present in the total suspended particulate matter emitted during the ring of ceramics. These measurements can explain the ndings of Hibbert et al (1999) 30 and later of Jones et al (2013) 31 who showed that signicant amounts of heavy metals are present in the blood of artisanal pottery workers. Albeit the importance of these ndings, to the best of our knowledge, no information on the size distribution or the size-resolved composition of the emitted particles is available.…”
Section: Introductionmentioning
confidence: 61%